Genome hypermobility by lateral transduction - Chen,J; Quiles-Puchalt,N; Chiang,YN; Bacigalupe,R; Fillol-Salom,A; Chee,MSJ; Fitzgerald,JR; Penades,JR (Science, 2018)
Genetic transduction is a major evolutionary force that underlies bacterial adaptation. Here we report that the temperate bacteriophages of Staphylococcus aureus engage in a distinct form of transduction we term lateral transduction. Staphylococcal prophages do not follow the previously described excision-replication-packaging pathway but instead excise late in their lytic program. Here, DNA packaging initiates in situ from integrated prophages, and large metameric spans including several hundred kilobases of the S. aureus genome are packaged in phage heads at very high frequency. In situ replication before DNA packaging creates multiple prophage genomes so that lateral-transducing particles form during normal phage maturation, transforming parts of the S. aureus chromosome into hypermobile regions of gene transfer.